Workflow for a Functional Assay of Candidate Effectors From Phytopathogens Using a TMV-GFP-based System - Cao, Peng; Shi, Haotian; Chen, Jialan; Cui, Langjun; Zhang, Meixiang; An, Yuyan (Bio-protocol, 2025)
The ability to efficiently screen plant pathogen effectors is crucial for understanding plant-pathogen interactions and developing disease-resistant crops. Traditional methods are often labor-intensive and time-consuming. Here, we present a robust, high-throughput screening assay using the tobacco mosaic virus-green fluorescent protein (TMV-GFP) vector system. The screening system combines the TMV-GFP vector and -mediated transient expression in the model plant . This system enables the rapid identification of effectors that interfere with plant immunity (both activation and suppression). The biological function of these effectors can be easily evaluated within six days by observing the GFP fluorescence signal using a UV lamp. This protocol significantly reduces the time required for screening and increases the throughput, making it suitable for large-scale studies. The method is versatile, cost-effective, and can be adapted to effectors with immune interference activity from various pathogens. Key features • A robust, cost-effective, and high-throughput functional screening system for plant pathogen effectors. • Utilizes the TMV-GFP vector for rapid monitoring of effector activity. • Evaluates the function of effectors within a few days using just a UV lamp. • Adaptable to both apoplastic and cytoplasmic effectors from various phytopathogens.